Pengaruh Dana Pihak Ketiga (DPK) Mudharabah Anggota dan Liability Lembaga Lain Terhadap Return On Equity (Study Pada Lembaga Keuangan Syariah Non Bank di Tulungagung dan Blitar) - Binti Nur Asiyah; Lantip Susilowati; Nur Aziz Muslim (Institut Agama Islam Negeri Madura, 2018)
This study is based on the limitations of non-bank syariah financial institutions (Baitul Maal wat Tamwil) in accessing funds from members. The Cooperative Act of 2012 provides an opportunity for Cooperatives to access funds from other institutions. This condition has an impact on profit performance for equity owners. If the profit is low then the institution's sustainability is threatened. The equity holder moves his funds into a more profitable business. This research aims to; 1) Analyzing the condition of Third Party Funds (DPK) mudharabah at BMT in Tulungagung and Blitar. 2) Analyzing other institutions' liability conditions in BMT Tulungagung and Blitar. 3). Analyzing the condition of return on equity at BMT in Tulungagung and Blitar. 4) Test the significant influence of Third Party Funds (DPK) mudharabah on return on equity at BMT in Tulungagung and Blitar. 5) Examining the significant influence of other institutions' liability on return on equity in BMT Tulungagung and Blitar. 6) Examine the significant influence of Third Party Funds (DPK) mudharabah and other institutional liability to return on equity in BMT Tulungagung and Blitar. This research was conducted with a quantitative approach and type of associative research. Data analysis was done by data normality test, classical assumption test (Multikolineritas, heterokedastisitas, autokorelasi), multiple regression test, hypothesis test, coefficient of determination test. The results of this study are 1). The condition of Third Party Funds (DPK) mudharabah members experience fluctuations in both BMT in Tulungagung, while in Blitar tend to decrease. 2) Liability of other institutions is more needed in BMT Blitar, than in Tulungagung. 3). Return on equity is greater on BMT in Blitar than in Tulungagung. 4) Mudharabah DPK has a positive but not statistically significant effect on the return on equity of non-bank Islamic financial institutions in Tulungagung and Blitar. 5) Liability to other institutions gives a negative and not statistically significant effect on the return on equity of non-bank Islamic financial institutions in Tulungagung and Blitar. 6) Simultaneously mudharabah DPK variable and liability at other institution give influence and not statistically significant to return on equity BMT in Tulungagung and Blitar